2015
DOI: 10.1128/mbio.02357-14
|View full text |Cite
|
Sign up to set email alerts
|

Novel Components of the Toxoplasma Inner Membrane Complex Revealed by BioID

Abstract: The inner membrane complex (IMC) of Toxoplasma gondii is a peripheral membrane system that is composed of flattened alveolar sacs that underlie the plasma membrane, coupled to a supporting cytoskeletal network. The IMC plays important roles in parasite replication, motility, and host cell invasion. Despite these central roles in the biology of the parasite, the proteins that constitute the IMC are largely unknown. In this study, we have adapted a technique named proximity-dependent biotin identification (BioID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
206
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(209 citation statements)
references
References 57 publications
(106 reference statements)
2
206
0
1
Order By: Relevance
“…To confirm that IMC proteins are modified by ubiquitin, we performed immunoprecipitation (IP) of epitope-tagged IMC proteins (Beck et al, 2010; Chen et al, 2014) from intracellular tachyzoites followed by Western blot using anti-ubiquitin antibodies (Figure 4A). To prevent degradation of polyubiquitinated proteins, intracellular parasites were treated with the proteasome inhibitor MG-132 before lysate preparation (Shaw et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that IMC proteins are modified by ubiquitin, we performed immunoprecipitation (IP) of epitope-tagged IMC proteins (Beck et al, 2010; Chen et al, 2014) from intracellular tachyzoites followed by Western blot using anti-ubiquitin antibodies (Figure 4A). To prevent degradation of polyubiquitinated proteins, intracellular parasites were treated with the proteasome inhibitor MG-132 before lysate preparation (Shaw et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…To avoid division by 0 we used 0.2 as an arbitrary value in those cases where no trace of the protein was detected in the HA- fraction. This list includes proteins already described to be palmitoylated (Table S1 highlighted in blue) such as HSP20 [12], GAP45 and AMA1 [15] and members of the ISP family [9], those predicted to be palmitoylated but without experimental evidence (Table S1 highlighted in grey) such as members of the ISC (IMC structure component), IMC (inner membrane complex) and AC (apical cap) families [32], and those that share homology to known S-acylated proteins from Plasmodium falciparum , a related organism, such as 14-3-3, Hsp70 and proteins of the CDPK family [33] (Table S1 highlighted in green). We also identified TGME49_213550 (TgDHHC 4), TGME49_249380 (TgDHHC13) and TGME49_278850 (TgDHHC2) which are DHHC S-acyl transferases [18].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding function and biological processes in which palmitoylated proteins are involved, most of them cluster into groups including metabolic and energy-related processes and protein translation (Figure 2B). However, it is evident that the modification affects the majority of cellular functions since we were able to identify proteins involved in a plethora of roles: from signaling (CDPK3), to gliding motility (myosin A, GAP45 and various filament-like alveolins, members of the recently described IMC, AC and ISC families [32]), translation (translation initiation factor eIF-5A and translation elongation factor 2), among others. Some of these proteins have been previously reported to be palmitoylated: in the case of TgCDPK3, studies have shown that palmitoylation not only occurs but it also affects the localization of the protein and thus its function in the parasite’s ability to egress the host-cell [35].…”
Section: Resultsmentioning
confidence: 99%
“…The method also has been used to screen for proteins involved in the Hippo signaling pathway (Couzens et al, 2013). Additionally, BioID has been applied to a secreted protein of Chlamydia psittaci that targets the nuclear envelope (Mojica et al, 2015), used to identify novel components of the inner membrane complex of Toxoplasma gondii (Chen et al, 2015), analyzing HIV-1 Gag protein interactions (Ritchie et al, 2015), and utilized in detecting c-MYC interacting partners in cultured cells and mice xenograft tumors (Dingar et al, 2014). …”
Section: Introductionmentioning
confidence: 99%